PENGARUH PERSEPSI HARGA, KUALITAS DAN PEMASARAN VIA ONLINE TERHADAP KEPUTUSAN PEMBELIAN PRODUK BOSTER TEA - Fahrurrozi Rahman; Hariri Hariri (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This research was aimed to investigate the influence of online marketing and perception of the price to the decision of the purchase of "three second" products in  students of the faculty the economic 2013-2015 UNISMA .The population of this research is all students of the faculty the economic 2013-2015 UNISMA. Sample taken by using the method accidental sampling in order to obtain 94 of respondents who qualified in the sample .This research using the primary data and and multiple regression analysis method.The result of this research shows that the variable of online marketing has positive and insignificant effect to the decision of the purchase , the  variable price of perception has  negative and significant effect to the decision of the purchase .Simultaneously variable marketing online , and perception of the price have significant influence to the decision of the purchase .Keywords: Perception Of The Price, Quality, Online Marketing, Decision Of The Purchase.